What Happened to the Phycobilisome? - Green, Beverley R. (Biomolecules, 2019)
The phycobilisome (PBS) is the major light-harvesting complex of photosynthesis in cyanobacteria, red algae, and glaucophyte algae. In spite of the fact that it is very well structured to absorb light and transfer it efficiently to photosynthetic reaction centers, it has been completely lost in the green algae and plants. It is difficult to see how selection alone could account for such a major loss. An alternative scenario takes into account the role of chance, enabled by (contingent on) the evolution of an alternative antenna system early in the diversification of the three lineages from the first photosynthetic eukaryote.